2009
DOI: 10.1186/bf03352939
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of ionospheric gradients for GAGAN application

Abstract: To cater to the needs of aviation applications, GPS Aided GEO Augmented Navigation (GAGAN) system is being implemented over the Indian region. The most prominent parameter affecting the navigation accuracy of GAGAN is ionospheric delay which is a function of TEC. In the equatorial and low latitude regions such as India, TEC is often quite high with large spatial gradients. Carrier phase data from the GAGAN network of Indian TEC Stations is used for estimating ionospheric gradients in multiple viewing direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…The maximum ionosphere slope of 460. 4 [25]. But, at low latitudes, the decorrelation of ionosphere is comparatively large, this is evident from the data analysis.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…The maximum ionosphere slope of 460. 4 [25]. But, at low latitudes, the decorrelation of ionosphere is comparatively large, this is evident from the data analysis.…”
Section: Resultsmentioning
confidence: 70%
“…For example, Figure 16 shows the MIEVs obtained for nC 4 combinations at an epoch (9.35 Hrs LT) on 9th March 2012 for which the MIEV is 184.4 m due to 'all-in-view' satellites. At this epoch, it is observed that the number of total visible satellites are '11' (SV PRN 1, 3, 6, 11, 14, 16, 20, 21, 30, 31 and 32) at this epoch.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial gradient of TEC utilized in this study was computed using Eq. (1) (Lee et al, 2007;Ravi Chandra et al, 2009;Cesaroni et al, 2015).…”
Section: Data and Analysis Methodsmentioning
confidence: 99%
“…Recently, Seba et al (2018) investigated the relationship between equatorial ionization anomaly and nighttime ESF over the East Africa longitudinal sector using data from ground-based Global Positioning System (GPS) stations and a horizontal meridional neutral wind model. To identify signals which suffer severely from the ionospheric gradient, Ravi Chandra et al (2009) andRungraengwajiake et al (2015) used rate of change of TEC (ROT) and rate of change of TEC index (ROTI). From the definition, however, ROTI mixes both the spatial and temporal gradients of TEC variations.…”
mentioning
confidence: 99%